Platform business Eco-model evolution: case study on KakaoTalk in Korea - Junghee Han; Okjoo Cho (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
Platform business is often regarded as notable examples of successful businesses model in the mobile industry. The purpose of this study is to find the determinants of successful platform business, through the case study of KakaoTalk, a representative fast growing social platform in Korea. This study also discusses how to create a value proposition and how organizations using the platform can cooperate. The case analysis indicates that a preparation, spread, evolution (PSE) curve is a successful platform business evolution. The PSE curve is composed of three phases: a preparation phase that establishes the platform and sets the target group, a spread phase where the firm provides killer content, such as KakaoGame, a low pricing strategy, and reinforcement of the platform rules in the early stages of the platform; and an evolution phase where the platform continues to evolve. This study proposes a platform evolution pattern that involves the PSE curve in order to form successful platform. This study contributes to the innovation for social platform businesses.
Keywords: 650; KakaoTalk; Business model; Business model innovation; Platform; Korea